The road back home [compact disc] - McKennitt, Loreena, 1957- (Quinlan Road, 2024)
"There are many ways to define the word home... the structure in which we live, but also the cultural expressions of community which somehow reach into our hearts and souls without us completely understanding why. If it is true, home is where the heart is, well my heart has returned to a place I knew I always loved. The Road Back Home." Loreena McKennitt.